Detecção molecular e sorológica de Flavivirus emergentes em roedores e primatas: relação entre patógeno, hospedeiro e ambiente - Poliana de Oliveira Figueiredo (2019)
The occurrence of emerging infectious diseases (EID) has been increasing in recent years, and this emergence is associated with social, economic, and mainly environmental determinants. Most of these diseases are of zoonotic origin and among the risk factors associated with this transmission are the opportunity for contact and phylogenetic proximity of reservoirs and / or animal hosts with humans. Rodents and non-human primates are amplifiers or reservoirs of zoonotic pathogens, and in many places live in close contact with the human population and domestic animals, these animals can act as a bridge between the wild, urban. In this way, this project hypothesized the circulation of DENV in rodents or primates as well as the circulation of yellow fever in other animals besides primates, with rodents being the candidate animals. Dengue is currently one of the most important diseases in terms of morbidity, mortality and national economic impact. In addition, Brazil has recently experienced one of the largest outbreaks of yellow fever in its history, with more than 1000 confirmed cases, a case fatality rate higher than previous years, and there is still a large population contingent without adequate vaccine coverage. Considering this scenario, this study aimed to prospect for Dengue virus (DENV) and Yellow fever virus (YFV) in rodentia and non-human primates collected in forest, urban and rural environments. Through molecular and sorological prospecting of samples from small rodents, capybaras (Hydrochoerus hydrochaeris) and samples of non-human primates were analyzed. No positive rodent samples were detected for DENV and YFV, and no evidence of DENV circulation in primates. The absence of detection, compared to other studies, can be attributed to the difference in the sample number of the analyzed collections, the species analyzed and the collection sites that could be reflecting different ecological conditions of each analyzed area. In relation to prospecting for yellow fever in primates, two positive animals were detected. Both animals are of the species Callicebus personatus and were collected during the outbreak of yellow fever in the state of Minas Gerais. Phylogenetic analyzes constructed through 205 bp of NS5 and 945 bp of the CprM region demonstrated that these samples are grouped together with the South American genotype 1, being more closely related to the samples characterized during the current outbreak of yellow fever experienced in Brazil. In addition, necropsy of several organs have shown macroscopic changes, compatible with YFV viral infection. The molecular data associated with macroscopic data contribute to fill some gaps related to the lack of information regarding the course of infection in non-human primates. A temporal correlation between human cases and YFV epizootics in Minas Gerais in 2017 demonstrated an overlap of cases and that these clusters are grouped in 2 clusters that occurred mainly in regions with low vaccination coverage, pointing to a need for better surveillance and prevention policies. Serological survey of Flavivirus in non-human primates showed that one of the animals tested showed anti-flavivirus antibodies, thus indicating a previous contact of this animal with virus.